Design and Planning of The Porang Supply Chain in South Sumatra - Agustina Bidarti; Yulius Yulius; Erni Purbiyanti (Universitas Muhammadiyah Malang, 2021)
The length of the existing porang (Amorphopallus Muelleri B) supply chain is causing a problem on porang farmers in South Sumatra. The purpose of this research was to construct a P4S Karya Tani porang supply chain with two evaluation steps. First beginning, identify the potential demand for porang in South Sumatra from either the demand and supply perspective. Second, consider the challenges of maximizing market demand in the porang supply chain in South Sumatra. The research employed a qualitative descriptive method with a philosophical approach to supply chain management theory. Based on the discussion, P4S as evaluated the porang supply chain design, determining that small and large traders must be eliminated as intermediaries, allowing them to sell porang raw materials direct to consumers and agro-industry enterprises that export porang. All elements, including that of the local government, Sriwijaya University, the corporate sector, and banking institutions, should be involved in the P4S porang supply chain planning. This collaboration is crucial in order to connect and transform the paradigm of direct sales to consumers, enabling P4S porang farmers to sell to the nearest consumer, PT PIP in South Lampung, via a contract farming system.